Position of Chosen European Union Countries in Respect of Financial Efficiency of Higher Education in the Area of Didactics - Anna Ćwiąkała-Małys; Monika Mościbrodzka (Economic and Environmental Studies (E&ES), 2017)
This article is continuation of the authors' research on financial efficiency evaluation in higher education in the area of didactics in countries that belong to European Union. On the basis of the results of researches, in which a non-parametric approach was used, a classification of member countries into uniform groups has been conducted with reference to researched feature.
Keywords: C14; C38; I21; I23; 330; financial efficiency; didactical process; non-parametric methods; Ward method; European Union higher education